U Kapaydiman nu Kaydian a Ivatan: Suicide Cases in the Province of Batanes - Billote, William Jo Se; Ponce, Ryan; Ponce, Trixie Elaine; Alcantara, Anthony; Ballada, Fay Ann; Calma, Trisha Mhay; Duya, Alyson Dessiree; Gasilao, Allysa Mae; Salengua, Marcela; Villegas, John Russell (JPAIR Multidisciplinary Research, 2022)
Suicide has received attention in the global public health arena and its effect has a prolonged-lasting psychological trauma on friends and relatives. This prompted the researchers to systematically analyze the possible underreporting of suicide cases, particularly in the province of Batanes. There are no studies of trends in the incidence of suicide that have been undertaken in the province. Thus, it aimed to provide a complete picture of the problem’s size and facilitate better-informed decisions concerning prevention priorities such as high-risk age or sex groups and the most common suicide methods. The study used a descriptive research design and inventory questionnaires to gather data from six (6) municipal civil registrars from the different municipalities in the province of Batanes. Based on the results, causes of death are asphyxiation, gunshot, and alcohol intoxication, and the municipality with the highest committed cases is Basco, Batanes. Additionally, males are more inclined to commit suicide than females, and young and middle-aged individuals have more committed self-inflicted cases than older people. It has also been found that suicide cases have risen from 2010 to the present.